PENGEMBANGAN APLIKASI ABSENSI BERBASIS WEB MENGGUNAKAN FACE RECOGNITION - M. Fauzi Isputrawan; Suriyanti Suriyanti (Universitas Teknokrat Indonesia, 2023)
Abstract In the conditions of the Covid-19 pandemic, which had an impact on company activities, such as social distancing, there were several company employees working from home. This work-from-home activity itself is not easy to implement, especially for companies that do not yet have a supporting system. The same condition with some of Company that still use the traditional method in employee management. The use of a website-based personnel management application recommended by the author can assist in submitting leave, making reports, storing, processing personnel data, and attendance with face recognition. This attendance application uses the PHP programming language with the SDLC development method and the waterfall model. From the results of the research conducted, it has been concluded that this personnel management application helps solve problems at several companies in personnel management activities. In the development of the application made to adjust to the problems and needs of the organization as well as the application uses a simple design to speed up users' learning of how to use the application when the application is implemented in the company. In the future, the application is expected to be developed according to technological developments so that the application still exists and can be used for an extended period of time. Keywords: Attendance, Application, Face Recognition, Website, SDLC, PHP